A phylogeny of the Brachyopoidea (Temnospondyli, Stereospondyli) - Warren, Anne (2000)
In the thirty years since the last comprehensive review of the Brachyopidae many new brachyopid genera have been described and several different phylogenies proposed. This paper provides revised diagnoses of the Brachyopidae, their sister taxon, the Chigutisauridae, and the Brachyopoidea, erects a new higher taxon, Brachyopomorpha to include stem brachyopoids, and reviews the status of all material referred at one time to these taxa. In it we present revised illustrations of the first described member of the Brachyopidae and clarify parts of the morphology of it and other members of the Brachyopoidea including especially the mandible and postcranial skeleton. A new genus and species, Vigilius wellesi, is proposed for the skull of Hadrokkosaurus bradyi as the holotype of H. bradyi, a mandible, cannot be positively associated with the skull. A phylogenetic analysis including most taxa and all putative outgroups confirms the Chigutisauridae as sister group to the Brachyopidae, forming the Brachyopoidea. Bothriceps australis becomes a sister taxon to the Brachyopoidea. Xenobrachyops allos and Keratobrachyops australis are the most plesiomorphic members of the Brachyopidae and Chigutisauridae respectively.